2018
DOI: 10.1111/1753-6405.12779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Make Healthy Normal mass media campaign (Phase 1) on knowledge, attitudes and behaviours: a cohort study

Abstract: Mass media campaigns can play a role in obesity prevention but robust evaluations are needed to identify the characteristics of effective campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…In phase one (2015–2017), the target audience was all NSW adults. Evaluation of phase one found that it was effective at increasing knowledge of physical activity recommendations and the health effects of overweight and obesity but had no effect on behaviour ( Kite et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In phase one (2015–2017), the target audience was all NSW adults. Evaluation of phase one found that it was effective at increasing knowledge of physical activity recommendations and the health effects of overweight and obesity but had no effect on behaviour ( Kite et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we sought to determine whether (1) the HOEM that underpins the evaluation of MHN is a useful and valid predictive tool; and (2) the cascade of effects in the HOEM varies for different behavioural outcomes. Note that this study does not evaluate the campaign's effectiveness, which has been done elsewhere ( Kite et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth working with these media outlets to develop public educational programmes about dementia and to introduce the availability of dementia services in the region. A robust evaluation of these health education campaigns conducted via mass media should be carried out so that the impact of mass media campaigns on knowledge, attitudes, and behaviours can be assessed [23]. Another option for public education is social media (Facebook, WeChat, Instagram), as a substantial number of respondents would like to receive dementia information from these channels.…”
Section: Conceptual Framework Of Dementia Literacymentioning
confidence: 99%
“…Phase 1 of the campaign (2015-2016) targeted all NSW adults, while Phase 2 (2016-2018) focused on males aged 35 to 54 years and parents with children aged 5 to 12 years. Although the majority of the campaign spend was allocated to advertising on two television commercials, the campaign also made use of a number of other communication channels, including out-of-home advertising (e.g., bus sides, billboards), online advertising, community events, and social media, particularly Facebook. More details on the campaign and its evaluation are available elsewhere (Kite et al, 2018).…”
Section: The Make Healthy Normal (Mhn) Campaignmentioning
confidence: 99%